Bioassay-Guided Fractionation and Biological Activity of Cardenolides from Streptocaulon juventas - Xu, Yunhui; Xu, Jian; Zhu, Wanfang; Yan, Yanling; Jiang, Xueyang; Xie, Zijian; Feng, Feng; Zhang, Jie (Planta Medica, 2023)
The discovery that Na/K-ATPase acts as a signal transducer led us to investigate the structural diversity of cardiotonic steroids and study their ligand effects. By applying Na/K-ATPase activity assay-guided fractionation, we isolated a total of 20 cardiotonic steroids from Streptocaulon juventas, including an undescribed juventasoside B (10) and 19 known cardiotonic steroids. Their structures have been elucidated. Using our platform of purified Na/K-ATPase and an LLC-PK1 cell model, we found that 10, at a concentration that induces less than 10% Na/K-ATPase inhibition, can stimulate the Na/K-ATPase/Src receptor complex and selectively activate downstream pathways, ultimately altering prostate cancer cell growth. By assessing the ligand effect of the isolated cardiotonic steroids, we found that the regulation of cell viability by the isolated cardiotonic steroids was not associated with their inhibitory potencies against Na/K-ATPase activity but reflected their ligand-binding affinity to the Na/K-ATPase receptor. Based on this discovery, we identified a unique active cardiotonic steroid, digitoxigenin (1), and verified that it can protect LLC-PK1 cells from hypoxic injury, implicating its potential use in ischemia/reperfusion injury and inducing collagen synthesis in primary human dermal fibroblast cells, and implicating that compound 2 is the molecular basis of the wound healing activity of S. juventas.
Keywords: Streptocaulon juventas; Asclepiadaceace; cardiotonic steroids; Na/K-ATPase